In2S3‐Polymer Hybrid Gels Derived from In(III) Metal–Organic Gels for Dye Adsorption, Photodegradation, and Bacteria Removal. Issue 8 (23rd June 2021) - Li, Botian; Zhou, Xue; Yan, Bo; Li, Yingchao; Ye, Haimu; Huang, Guoyong; Zhou, Qiong
Abstract: Currently, the treatment of wastewater that contains organic dyes and bacteria attracts a considerable amount of attention, and the fabrication of photoinduced catalytic materials to address the problem is still a challenge. In this work, indium(III) sulfide hybrid gels are prepared by in situ polymerization and sulfurization using In(III) metal–organic gels as sacrificial templates. Two In(III) metal–organic gels are fabricated by the coordination interaction between multitopic pyridyl ligands and indium ions, where the assembled structure of the gel templates can be tuned by employing different multitopic ligands to obtain the networks of nanofibers and nanoparticles. After templated fabrication, the resulting In2 S3 ‐polymer hybrid gels show improved mechanical strength, and can be used as novel photocatalysts for the photodegradation of organic dyes, such as rhodamine B and methylene blue, and efficient adsorbents for the adsorption of anionic dyes, such as Congo red. Experiments that involve pure and mixed bacteria demonstrate the bacteria‐removing activities of the hybrid gels due to their electrostatic adsorption and photoinduced sterilization of the bacteria. Therefore, this new kind of hybrid gel might have potential applications in the photoinduced purification of water by scavenging organic dyes and bacteria in the aqueous phase. Abstract : In2 S3 ‐polymer hybrid gels are prepared by template synthesis using In(III) metal–organic gels as templates. The polymeric network imparts the hybrid gel promoted mechanical strength; thus the hybrid gels exhibit excellent performance of scavenging organic dyes based on adsorption and photocatalysis. The hybrid gels can efficiently remove bacteria, thus might have potential application in photocatalysis and water treatment.